Optimal injection timing and gas mixture proportion for enhancing coalbed methane recovery. (1st May 2021) - Fan, Zhanglei; Fan, Gangwei; Zhang, Dongsheng; Zhang, Lei; Zhang, Shuai; Liang, Shuaishuai; Yu, Wei
Abstract: Optimal injection timing and gas mixture proportion have great influence on CO2 geological sequestration and improvement of recovery. The refined Thermo-hydro-mechanical (THM) coupling model including an improved permeability model was first validated by matching with historical data, and then applied to the simulation of gas mixture enhanced coalbed methane recovery (GM-ECBM). Results show that higher internal expansion coefficients and elastic modulus reduction ratios can weaken the large-scale matrix strain swelling and improve optimal CO2 composition, as do the effect of smaller matrix diffusivity. The trend of CH4 production in dehydration period was controlled by the diffusion ability of matrix, which was used to account for the different gas production trends using THM coupling model for the first time. The key of GM-ECBM was to produce and utilize the peak value of initial gas production rate while controlling the production rate of N2 +CO2 . For the constant-composition injection, the optimal CO2 composition and cumulative recovery rate dropped with the injection delay. Starting with a lower CO2 concentration input, an increase-composition scheme with 1000 days delay witnessed high recovery rate (65.7%) and high CO2 storage (8.21 mega cubic meters), in which CO2 composition was gradually injected at a high-to-low rate. Highlights: A refined THM model for gas mixture enhanced coalbed methane recovery is established. The reason for different production rate trends is verified for the first time. The key of GM-ECBM is to control N2 +CO2 rate and utilize initial gas production peak. The optimal CO2 composition drop with injection delay for constant-composition. An increase-composition scheme with 1000 days delay is proposed.